2008
DOI: 10.1021/ef700562c
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate Mixture Model for the Thermophysical Properties of Synthetic Aviation Fuel S-8: Explicit Application of the Advanced Distillation Curve

Abstract: Fluid volatility is an important property of liquid fuels that previously has not been adequately addressed in the development of surrogate models for the thermophysical properties of these fluids. Especially important and timely is the development of surrogates for aviation fuels. In the present context, models refer to mathematical descriptions such as equations of state that provide a predictive capability. In this work, we demonstrate how the incorporation of volatility data, in the form of a distillation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
189
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(192 citation statements)
references
References 37 publications
2
189
1
Order By: Relevance
“…With regard to physical properties, experimental and modeling characterization of a series of iso-alkanes may be helpful to properly represent the distillation curve of diesel fuel. Huber et al [42] have found that isoalkanes need to be included in a surrogate to properly simulate the thermal conductivity of liquid diesel fuel.…”
Section: Isoalkanesmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to physical properties, experimental and modeling characterization of a series of iso-alkanes may be helpful to properly represent the distillation curve of diesel fuel. Huber et al [42] have found that isoalkanes need to be included in a surrogate to properly simulate the thermal conductivity of liquid diesel fuel.…”
Section: Isoalkanesmentioning
confidence: 99%
“…A low and high molecular weight compound was included in the surrogate to properly predict the initial boiling point and the tail of the target distallation curve. Later, they applied the same approach and derived a seven-component surrogate fuel for a Fischer-Tropsch S-8 jet fuel [42]. The seven components were n-nonane, 2,6-dimethyloctane, 3-methyldecane, n-tridecane, n-tetradecane, npentadecane and n-hexadecane.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…Detailed compositional reports by Bruno and coworkers [8,9] for turbine fuels, such as GTL, CTL, SPK, and biomass-derived fuels indicate that di-methylated alkanes represent an important fraction of the fuel composition. Huber et al [10] have also proposed 2,6-dimethyloctane as a surrogate component for synthetic aviation fuel S-8. …”
mentioning
confidence: 99%
“…We have applied this method to a wide variety of gasoline, diesel fuel, aviation fuel and rocket propellant mixtures (Bruno and Smith, 2006b;Bruno et al, 2009a;2009c;2009d;Hadler et al, 2009;Ott et al, 2008a;2008c;2008d;Smith and Bruno, 2007c;Lovestead and Bruno, 2009a). Moreover, we have used the measurements derived from this method as the basis for the development of thermophysical property models for many of these fluids (Huber et al, 2008a;.…”
Section: Advanced Distillation Curve Metrologymentioning
confidence: 99%